2021
DOI: 10.1093/cid/ciab991
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Persistent Symptoms in Children With Polymerase Chain Reaction (PCR)–Confirmed Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection Compared With Test-Negative Children in England: Active, Prospective, National Surveillance

Abstract: Background Most children recover quickly after COVID-19, but some may have on-going symptoms. Follow-up studies have been limited by small sample sizes and lack of appropriate controls Methods We used national testing data to identify children aged 2-16 years with a SARS-CoV-2 PCR test during 01-07 January 2021 and randomly selected1,500 PCR-positive cases and 1,500 matched PCR-negative controls. Parents were asked to complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(91 citation statements)
references
References 27 publications
3
88
0
Order By: Relevance
“…The controls were chosen in a very different way among studies, which might have introduced significant heterogeneity. The following were the different definitions of controls: 1) children with other infections (e.g., common cold, pharyngotonsillitis, gastrointestinal, urinary tract infections, pneumonia of bacteria or unknown origin) 16 ; 2) children with no antibodies testing 18 mixed with other children with other infections 16 ; 3) children with a negative antibody test 19 , 4) children with a negative PCR test that were symptomatic 20 ; and 5) children who did not have a positive test recorded in the database 14 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The controls were chosen in a very different way among studies, which might have introduced significant heterogeneity. The following were the different definitions of controls: 1) children with other infections (e.g., common cold, pharyngotonsillitis, gastrointestinal, urinary tract infections, pneumonia of bacteria or unknown origin) 16 ; 2) children with no antibodies testing 18 mixed with other children with other infections 16 ; 3) children with a negative antibody test 19 , 4) children with a negative PCR test that were symptomatic 20 ; and 5) children who did not have a positive test recorded in the database 14 .…”
Section: Resultsmentioning
confidence: 99%
“…The adjustments among studies also varied. Several studies adjusted their OR by age, sex, ethnicity, socioeconomic status, and comorbidities 20 . However age and sex 14 only adjusted for sex, only age 16 only adjusted for age, and Knoke et al did not adjust, or by OR without adjusting previous conditions 18 (Supplemental Figures 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis reveals that pediatric patients, despite apparent clinical recovery at discharge, had obvious behavioral problems when evaluated approximately two months later. Extensive research has examined the mental health burden in adults discharged from hospital with COVID-19 in China ( Chen et al, 2020 ; Chen, Huang, et al, 2021 ; Chen, Ju, et al, 2021 ; Huang, Huang, et al, 2021 ; Huang, Xu, et al, 2021 ; Huang, Zhuang, et al, 2021 ; Ju et al, 2021 ; Liang et al, 2020 ; Liu, Bao, et al, 2020 ; Liu, Baumeister, et al, 2020 ; Putri et al, 2021 ; Qu et al, 2021 ; Tu et al, 2021 ; Wu, Chen, et al, 2020 ; Wu, Hu, et al, 2020 ; Xiong, Xu, et al, 2021 ; Xiong, Zhong, et al, 2021 ; Yuan et al, 2020 ), Italy ( Mattioli et al, 2021 ; Tomasoni et al, 2021 ), Australia ( Darley et al, 2021 ; Rass et al, 2021 ), Netherlands ( de Graaf et al, 2021 ; Vlake et al, 2021 ), the UK ( Halpin et al, 2021 ; Zavala et al, 2021 ), France ( Garrigues et al, 2020 ; Horn et al, 2021 ; Morin et al, 2021 ), Germany ( Augustin et al, 2021 ; Daher et al, 2020 ), Iran ( Khademi et al, 2021 ; Mirfazeli et al, 2022 ), Egypt ( Kamal et al, 2021 ), Brazil ( Damiano et al, 2022 ; Todt et al, 2021 ), the USA ( Daugherty et al, 2021 ; Graham et al, 2021 ; Jovanoski et al, 2021 ; Martillo et al, 2021 ), and Korea ( Chang & Park, 2020 ) (see details in e Table B), reporting substantial psychological distress in the first few months after infection. However, there is limited information available on pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Liu and colleagues assessed children (aged 5–18 years) from Wuhan, China, who had been hospitalized with COVID-19 infection, and found significant symptoms of depression and anxiety in 15.8% and 31.6%, respectively ( Liu, Liu, et al, 2021 ). A study from the UK reported that children with symptomatic COVID-19 had a slightly higher prevalence of ongoing symptoms than symptomatic controls ( Zavala et al, 2021 ). This might be due to the relatively long COVID-19 isolation period, which prevents infected children from immediately returning home to their family.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] While there is an increasing understanding of the multi-organ damage of Covid-19 beyond the acute phase of infection 5 , the nature, frequency and definition of post-acute sequelae in children and adolescents still remains undetermined with a discrepancy in clinical appearance and objective findings. 6 A major proportion of pediatric studies have lately prioritized research in mental health issues during the Covid-19 pandemic [7][8][9][10] , while other studies have already raised concerns on ongoing disease manifestations, including increased thrombotic state, microangiopathy and inflammation. [11][12][13] As the lung is a primary target of the SARS-CoV-2 virus, 14 computed tomography aided in the diagnosis of pulmonary manifestation of Covid-19 in adults.…”
Section: Introductionmentioning
confidence: 99%